Test-retest variability of left ventricular 4D flow cardiovascular magnetic resonance measurements in healthy subjects - Stoll, Victoria M.; Loudon, Margaret; Eriksson, Jonatan; Bissell, Malenka M.; Dyverfeldt, Petter; Ebbers, Tino; Myerson, Saul G.; Neubauer, Stefan; Carlhäll, Carl- Johan; Hess, Aaron T. (Journal of cardiovascular magnetic resonance, 2018)
Background Quantification and visualisation of left ventricular (LV) blood flow is afforded by three-dimensional, time resolved phase contrast cardiovascular magnetic resonance (CMR 4D flow). However, few data exist upon the repeatability and variability of these parameters in a healthy population. We aimed to assess the repeatability and variability over time of LV 4D CMR flow measurements. Methods Forty five controls underwent CMR 4D flow data acquisition. Of these, 10 underwent a second scan within the same visit (scan-rescan), 25 returned for a second visit (interval scan; median interval 52 days, IQR 28–57 days). The LV-end diastolic volume (EDV) was divided into four flow components: 1) Direct flow: inflow that passes directly to ejection; 2) Retained inflow: inflow that enters and resides within the LV; 3) Delayed ejection flow: starts within the LV and is ejected and 4) Residual volume: blood that resides within the LV for > 2 cardiac cycles. Each flow components’ volume was related to the EDV (volume-ratio). The kinetic energy at end-diastole (ED) was measured and divided by the components’ volume. Results The dominant flow component in all 45 controls was the direct flow (volume ratio 38 ± 4%) followed by the residual volume (30 ± 4%), then delayed ejection flow (16 ± 3%) and retained inflow (16 ± 4%). The kinetic energy at ED for each component was direct flow (7.8 ± 3.0 microJ/ml), retained inflow (4.1 ± 2.0 microJ/ml), delayed ejection flow (6.3 ± 2.3 microJ/ml) and the residual volume (1.2 ± 0.5 microJ/ml). The coefficients of variation for the scan-rescan ranged from 2.5%–9.2% for the flow components’ volume ratio and between 13.5%–17.7% for the kinetic energy. The interval scan results showed higher coefficients of variation with values from 6.2–16.1% for the flow components’ volume ratio and 16.9–29.0% for the kinetic energy of the flow components. Conclusion LV flow components’ volume and their associated kinetic energy values are repeatable and stable within a population over time. However, the variability of these measurements in individuals over time is greater than can be attributed to sources of error in the data acquisition and analysis, suggesting that additional physiological factors may influence LV flow measurements.